Optical waveguide and method for manufacturing an optical waveguide

JP2026170501APending Publication Date: 2026-10-22NISSAN CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023141399
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0010】 本発明の光導波路は、大気下にて150℃、1000時間保管する高温耐久試験前後における波長1.31μmの光の伝搬損失値の変化率が10%以下であり、すなわち高温環境下において経時でコア/クラッドの屈折率変化が生じ難く、伝搬損失値の変化が少ない、ひいては挿入損失値の変化が少ない信頼性の高い光導波路を提供することができる。 また本発明の光導波路の製造方法は、高温環境下において経時でコア/クラッドの屈折率変化が生じ難く、伝搬損失値の変化が少ない、結果として挿入損失値の変化が少ない高い信頼性を有する光導波路を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170501000001_ABST
    Figure 2026170501000001_ABST
Patent Text Reader

Abstract

To provide an optical waveguide that offers high reliability, possessing transparency and lithography characteristics in the optical communication wavelength band, as well as maintaining a constant refractive index of the core / cladding over time. [Solution] An optical waveguide comprising a core, a cladding having a lower refractive index than the core that surrounds and covers the entire outer circumference thereof, and a protective layer on at least a portion of the outer surface of the cladding, An optical waveguide and a method for manufacturing the same, wherein, in a high-temperature endurance test of storage at 150°C for 1000 hours under atmospheric conditions, the propagation loss value of light with a wavelength of 1.31 μm after the test is less than 10% of the value before the test.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an optical waveguide, and more particularly to an optical waveguide that exhibits low change in propagation loss even when used in high-temperature environments and has high reliability. [Background technology]

[0002] In recent years, with advancements in technologies such as autonomous driving and artificial intelligence, and the anticipated technological innovation from 5G to 6G communication, the amount of data used on communication lines has increased dramatically. As a result, various research projects are underway to realize low-power consumption and massive data processing, thereby achieving ultra-high-speed, high-capacity communication. To achieve high speed, high capacity, and low power consumption in these communications, there is a shift from conventional electrical wiring using metal conductors to optical wiring. For example, board-edge optical interconnects, which mount photoelectric conversion units on the edge of a substrate (board) and connect optical fibers, have already been put into practical use as active optical cables (AOCs) that improve cable performance by using optical fibers between connectors. This trend has continued with onboard optical interconnects, which place the photoelectric conversion unit as a small onboard optical module on a substrate (board) near the processor, then on-package optical interconnects, which further miniaturize the photoelectric conversion unit and mount it on a package substrate on which an LSI chip is mounted, and finally onboard optical wiring, which forms an optical waveguide on the substrate (board) to transmit optical signals onboard. Mixed-signal optical substrates, waveguide-type optical splitters, and optical fiber / waveguide integrated optical modules have already been put into practical use.

[0003] In the optical wiring described above, optical waveguides using polymer materials are attracting attention because they are easy to process, low-cost, offer high flexibility in wiring, and allow for high-density connections. For example, an organic polymer optical waveguide formed from a photosensitive material has been proposed in which photolithography technology is used in all stages of formation, including the undercladding layer, the core phase which is the light-guiding portion, and the topcladding layer which covers the core phase, to complete the wiring within the package substrate. Photosensitive materials for forming optical waveguides are required to have a desired high refractive index, and in addition, to form fine optical waveguides on a substrate, film formability (such as film flatness), patterning properties (lithography characteristics), and high transparency in the communication wavelength band (for example, the infrared region: 1.31 μm band) are required .

[0004] For example, as the above photosensitive material for forming optical waveguides, a photosensitive epoxy resin composition for forming optical waveguides has been proposed which uses a polyfunctional epoxy resin having a bisphenol A skeleton, a solid semi-aliphatic difunctional epoxy resin, or other difunctional epoxy resins as the resin component and contains a photocationic polymerization initiator (see, for example, Patent Document 1). In addition, aiming at low propagation loss and high refractive index in the long-wavelength region, there are proposals for a composition for forming optical waveguides containing a specific reactive silsesquioxane compound and a specific fluorene compound (for example, Patent Document 2), and a composition for forming optical waveguides containing at least three epoxy compounds: a naphthalene group-containing difunctional fluorene epoxy compound intended to realize patterning properties, film formability and high refractive index, an alicyclic epoxy compound with 2 or fewer functional groups, and another aromatic epoxy compound with 2 or fewer functional groups other than the aforementioned fluorene epoxy compound (for example, Patent Document 3). [Prior Art Documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Unexamined Patent Application Publication No. 2020-20927 [Patent Document 2] International Publication No. 2018 / 199305 [Patent Document 3] International Publication No. 2023 / 277016 [Summary of the Invention] [Problems to be Solved by the Invention]

[0006] As described above, photosensitive materials for forming optical waveguides are required to have patterning properties, film-forming properties, high refractive index, and high transparency. In view of the recent trends toward high-speed communication and large capacity, optical waveguides are required to have high reliability, that is, the optical waveguide itself has a uniform structure (uniform refractive index), and the refractive index is less likely to change over time even in an environment that tends to reach high temperatures associated with high-speed communication, resulting in minimal change in propagation loss value.

[0007] The present invention addresses the problem of providing a highly reliable optical waveguide that, in addition to transparency and lithographic properties in the optical communication wavelength band, exhibits no change in the refractive index of the core / cladding over time in a high-temperature environment such as 150°C, with minimal change in propagation loss value, that is, minimal change in insertion loss value. [Means for Solving the Problems]

[0008] In order to solve the above problems, the present inventors have conducted diligent studies, and as a result, have found that the above problems can be solved by providing a protective layer on at least a part of the outer peripheral surface of the cladding in an optical waveguide having a core and a cladding that entirely surrounds and covers the outer periphery of the core, leading to the completion of the present invention.

[0009] That is, as a first aspect of the present invention, An optical waveguide comprising a core, a cladding that entirely surrounds and covers the outer periphery of the core and has a lower refractive index than the core, and a protective layer on at least a part of the outer peripheral surface of the cladding, In a high-temperature durability test involving storage at 150°C for 1000 hours in the atmosphere, the change rate of the propagation loss value for light with a wavelength of 1.31 μm after the test is 10% or less compared to the same value before the test. The present invention relates to the optical waveguide. As a second aspect, the present invention relates to the optical waveguide according to the first aspect, wherein the protective layer is a metal oxide-containing layer. As a third aspect, the present invention relates to the optical waveguide according to the second aspect, wherein the protective layer is a silicon dioxide-containing layer. As a fourth aspect, the core is composed of a cured product of a core-forming composition comprising (A) a reactive silsesquioxane compound and (B) a fluorene compound, Said (A) reactive silsesquioxane compound is a polycondensate of an alkoxysilane compound A represented by the following formula [1] and an alkoxysilane compound B represented by formula [2], The present invention relates to the optical waveguide according to the first aspect, wherein said (B) fluorene compound is a compound represented by the following formula [3].

Chemical Formula

Chemical Formula

Chemical Formula

[0010] The optical waveguide of the present invention exhibits a rate of change of 10% or less in the propagation loss value of light with a wavelength of 1.31 μm before and after a high-temperature durability test in which it is stored at 150°C for 1000 hours in air. In other words, it is possible to provide a highly reliable optical waveguide in which the refractive index of the core / cladding does not easily change over time in a high-temperature environment, resulting in little change in propagation loss value and, consequently, little change in insertion loss value. Furthermore, the optical waveguide manufacturing method of the present invention makes it possible to manufacture an optical waveguide with high reliability in which the refractive index of the core / cladding does not easily change over time in a high-temperature environment, the propagation loss value changes little, and as a result the insertion loss value changes little. [Brief explanation of the drawing]

[0011] [Figure 1] Figure 1 shows the time variation of insertion loss when optical waveguides 1-3 obtained from Examples 2-1, 2-2 and Comparative Example 2-1 are held at 150°C. [Modes for carrying out the invention]

[0012] In characterizing optical waveguides, it is desirable that they have low insertion losses, which are unavoidable when light passes through the waveguide. These include coupling losses that occur when light is introduced into and out of the waveguide, and propagation losses that occur when light passes through the waveguide (collectively referred to as insertion losses). These insertion losses are influenced by factors such as the transparency of the core / cladding, the flatness of the core / cladding interface, and the uniformity of the refractive index. However, changes in the refractive index of the core / cladding over time contribute to changes in the propagation loss value and, consequently, the insertion loss value, significantly affecting the reliability of the optical waveguide.

[0013] In light of the challenge of achieving high reliability in the optical waveguide described above, the inventors have been investigating the constituent materials and structure of the optical waveguide itself, focusing on the patternability, film formation properties, high refractive index, and high transparency of the core / cladding materials, as well as the uniformity of the refractive index in the core / cladding and the change in refractive index over time. Furthermore, regarding the change in refractive index of the core / cladding over time in high-temperature environments, we focused on the fact that the cladding is particularly susceptible to oxidation, and therefore adopted a configuration that includes a protective barrier layer to suppress the oxidation of the cladding.

[0014] [Optical waveguide] The optical waveguide of the present invention comprises a core, a cladding having a lower refractive index than the core that surrounds and covers the entire outer periphery of the core, and a protective layer on at least a portion of the outer surface of the cladding. Furthermore, in a high-temperature durability test in which the optical waveguide of the present invention is stored at 150°C for 1000 hours under atmospheric conditions, the propagation loss value of light with a wavelength of 1.31 μm after the test can be reduced by 10% or less, preferably 5% or less, compared to the same value before the test.

[0015] [Protective layer] The optical waveguide of the present invention is characterized by having a protective layer. The protective layer can be, for example, a metal oxide-containing layer. Examples of the metal oxides mentioned above include silicon dioxide (SiO2), titanium dioxide (TiO2), tungsten trioxide (WO3), zinc oxide (ZnO), zirconium oxide (ZrO2), niobium oxide (Nb2O5), and aluminum oxide (Al2O3). In particular, the protective layer in the present invention can be a silicon dioxide (SiO2)-containing layer. The protective layer can be formed on at least a portion of the outer surface of the cladding, for example, by sputtering, as will be described later.

[0016] [Core / Clad] In the optical waveguide of the present invention, the core can be made of a material having a refractive index greater than that of the formed cladding, and the material is not particularly limited. For example, in one embodiment, the core can be made of a cured product of the core-forming composition described later, and the cladding can be made of a cured product of the cladding-forming composition described later.

[0017] [Composition for core formation] The core in the optical waveguide of the present invention is, for example, made of a cured product of a core-forming composition comprising (A) a reactive silsesquioxane compound and (B) a fluorene compound.

[0018] <(A) Reactive silsesquioxane compound> The reactive silsesquioxane compound (A) used in the core-forming composition is a polycondensate of an alkoxysilane compound A with a specific structure and an alkoxysilane compound B with a specific structure, as described later. In more detail, these compounds are obtained by polycondensation of compounds A and B in the presence of an acid or a base.

[0019] [Alkoxysilane compound A] The aforementioned alkoxysilane compound A is a compound represented by the following formula [1]. [ka] In the above formula [1], Ar 1 R represents a phenyl group having at least one group having a polymerizable double bond, a naphthyl group having at least one group having a polymerizable double bond, or a biphenyl group having at least one group having a polymerizable double bond. 1 represents a methyl group or an ethyl group.

[0020] Ar 1 Examples of phenyl groups having at least one polymerizable double bond as represented by include 2-vinylphenyl group, 3-vinylphenyl group, 4-vinylphenyl group, 4-vinyloxyphenyl group, 4-allylphenyl group, 4-allyloxyphenyl group, and 4-isopropenylphenyl group. Ar 1 Examples of naphthyl groups having at least one polymerizable double bond as represented by include 4-vinylnaphthalen-1-yl group, 5-vinylnaphthalen-1-yl group, 6-vinylnaphthalen-2-yl group, 4-allyloxynaphthalen-1-yl group, 5-allyloxynaphthalen-1-yl group, 8-allyloxynaphthalen-1-yl group, 5-vinyloxynaphthalen-1-yl group, 4-allylnaphthalen-1-yl group, 5-allylnaphthalen-1-yl group, and 5-isopropenylnaphthalen-1-yl group. Ar 1 Examples of biphenyl groups having at least one group with a polymerizable double bond as represented by include 4'-vinyl-[1,1'-biphenyl]-2-yl group, 4'-vinyl-[1,1'-biphenyl]-3-yl group, 4'-vinyl-[1,1'-biphenyl]-4-yl group, 4'-vinyloxy-[1,1'-biphenyl]-4-yl group, 4'-allyl-[1,1'-biphenyl]-4-yl group, 4'-allyloxy-[1,1'-biphenyl]-4-yl group, and 4'-isopropenyl-[1,1'-biphenyl]-4-yl group.

[0021] Specific examples of compounds represented by the above formula [1] include, but are not limited to, trimethoxy(4-vinylphenyl)silane, triethoxy(4-vinylphenyl)silane, (4-isopropenylphenyl)trimethoxysilane, trimethoxy(4-vinyl-1-naphthyl)silane, and trimethoxy(4'-vinyl-[1,1'-biphenyl]-4-yl)silane.

[0022] [Alkoxysilane compound B] The aforementioned alkoxysilane compound B is a compound represented by the following formula [2]. [ka] In the above formula [2], Ar 2 R represents a phenyl group which may be substituted with an alkyl group having 1 to 6 carbon atoms, a condensed polycyclic aromatic hydrocarbon group which may be substituted with an alkyl group having 1 to 6 carbon atoms, or a hydrocarbon ring aggregate group in which multiple aromatic rings are directly bonded by single bonds (which may be substituted with alkyl groups having 1 to 6 carbon atoms), 2 represents a methyl group or an ethyl group.

[0023] Ar 2 Examples of phenyl groups that may be substituted with alkyl groups having 1 to 6 carbon atoms include phenyl group, o-tolyl group, m-tolyl group, p-tolyl group, and 2,4,6- Examples include trimethylphenyl groups and 4-tert-butylphenyl groups. Ar 2 Examples of condensed polycyclic aromatic hydrocarbon groups represented by include monovalent groups derived from naphthalene, phenanthrene, anthracene, triphenylene, pyrene, chrysene, naphthacene, biphenylene, and fluorene. Examples of hydrocarbon ring aggregate groups in which multiple aromatic rings are directly bonded by single bonds include monovalent groups derived from biphenyl, terphenyl, quaterphenyl, binaphthalene, phenylnaphthalene, phenylfluorene, and diphenylfluorene. In addition, examples of alkyl groups having 1 to 6 carbon atoms that may be present as substituents in the above-mentioned phenyl group, condensed polycyclic aromatic hydrocarbon group, and hydrocarbon ring aggregate group include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, cyclopentyl group, n-hexyl group, and cyclohexyl group. The above Ar 2 Among these, a phenyl group which may be substituted with an alkyl group having 1 to 6 carbon atoms is preferred.

[0024] Specific examples of compounds represented by the above formula [2] include, but are not limited to, trimethoxy(phenyl)silane, triethoxy(phenyl)silane, trimethoxy(p-tolyl)silane, trimethoxy(1-naphthyl)silane, triethoxy(1-naphthyl)silane, trimethoxy(2-naphthyl)silane, triethoxy(2-naphthyl)silane, trimethoxy(2-phenanthryl)silane, trimethoxy(3-phenanthryl)silane, trimethoxy(9-phenanthryl)silane, triethoxy(9-phenanthryl)silane, [1,1'-biphenyl]-4-yltrimethoxysilane, and [1,1'-biphenyl]-4-yltriethoxysilane.

[0025] Among the reactive silsesquioxane compounds, (A) a reactive silsesquioxane compound obtained by polycondensation of a compound represented by the following formula [1a] and a compound represented by the following formula [2a] in the presence of an acid or a base is preferred. [ka] In the above formula [1a], R 1 This expresses the same meaning as above. [ka] In the above formula [2a], R 2 This expresses the same meaning as above.

[0026] [Composition ratio of alkoxysilane compound A and alkoxysilane compound B] The molar ratio of alkoxysilane compound A, represented by formula [1], and alkoxysilane compound B, represented by formula [2], in the polycondensation reaction is not particularly limited, but to stabilize the physical properties of the cured product (core), a range of alkoxysilane compound A:alkoxysilane compound B = 5:1 to 1:5 is generally preferred. More preferably, the ratio is between 3:1 and 1:3. By setting the molar ratio of alkoxysilane compound A to the molars of alkoxysilane compound B to 5 or less, a cured product with a higher refractive index can be obtained. Furthermore, by setting the molar ratio of alkoxysilane compound A to the molars of alkoxysilane compound B to 1 / 5 or more, a sufficient crosslinking density can be obtained, and the dimensional stability against heat is further improved. The above-mentioned alkoxysilane compounds A and B can be selected and used as needed, and multiple types of compounds can also be used in combination. In this case, the molar ratio of the mixture is also such that the ratio of the total molar amount of alkoxysilane compound A to the total molar amount of alkoxysilane compound B falls within the above range.

[0027] [Acid or basic catalyst] The polycondensation reaction between alkoxysilane compound A represented by formula [1] and alkoxysilane compound B represented by formula [2] is preferably carried out in the presence of an acid or basic catalyst. The catalyst used in the polycondensation reaction described above is not particularly limited in type, as long as it dissolves in or is homogeneously dispersed in the solvent described later, and can be appropriately selected and used as needed. Examples of catalysts that can be used include, as acidic compounds, inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, and boric acid, and organic acids such as acetic acid and oxalic acid; as basic compounds, alkali metal hydroxides (sodium hydroxide, potassium hydroxide, etc.), alkaline earth metal hydroxides (magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, etc.), ammonium hydroxide, quaternary ammonium salts (tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, etc.), amines (triethylamine, etc.); and as fluoride salts, NH4F, NR4F (tetramethylammonium fluoride, tetrabutylammonium fluoride, etc.). Here, R is one or more groups selected from the group consisting of a hydrogen atom, a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, and a cyclic alkyl group having 3 to 12 carbon atoms. These catalysts can be used individually or in combination.

[0028] Among the catalysts mentioned above, one or more selected from the group consisting of hydrochloric acid, acetic acid, potassium hydroxide, calcium hydroxide, barium hydroxide, and tetraethylammonium hydroxide can be preferably used. The amount of catalyst used is 0.01 to 10% by mass, preferably 0.1 to 5% by mass, relative to the total mass of alkoxysilane compound A and alkoxysilane compound B. Using 0.01% by mass or more of catalyst allows the reaction to proceed more smoothly. Furthermore, considering economic efficiency, using 10% by mass or less is sufficient.

[0029] [Polycondensation reaction] (A) The reactive silsesquioxane compound is characterized by the structure of alkoxysilane compound A. The reactive group (polymerizable double bond) contained in alkoxysilane compound A readily polymerizes with radicals or cations, and exhibits high heat resistance after polymerization (after curing). The hydrolytic polycondensation reaction between alkoxysilane compound A and alkoxysilane compound B can be carried out without a solvent, but it is also possible to use a solvent that is inert to both alkoxysilane compounds (for example, tetrahydrofuran (THF), as described later) as the reaction solvent. Using a reaction solvent has the advantage of making the reaction system more homogeneous and allowing for a more stable polycondensation reaction.

[0030] (A) The synthesis reaction of reactive silsesquioxane compounds may be carried out without a solvent as described above, but it is acceptable to use a solvent to make the reaction more homogenized. The solvent is not particularly limited as long as it does not react with both alkoxysilane compounds and dissolves their polycondensate. Examples of such reaction solvents include ketones such as acetone and methyl ethyl ketone (MEK); aromatic hydrocarbons such as benzene, toluene, and xylene; ethers such as tetrahydrofuran (THF), 1,4-dioxane, diisopropyl ether, and cyclopentyl methyl ether (CPME); glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, and diethyl carbitol; and amides such as N-methyl-2-pyrrolidone (NMP) and N,N-dimethylformamide (DMF). These solvents can be used individually or in combination of two or more. They may be used together.

[0031] (A) The reactive silsesquioxane compound is obtained by hydrolysis polycondensation of alkoxysilane compound A represented by formula [1] and alkoxysilane compound B represented by formula [2] in the presence of an acid or basic catalyst. The reaction temperature for hydrolysis polycondensation is 20 to 150°C, more preferably 30 to 120°C. The reaction time is not particularly limited, as long as it is longer than the time required for the molecular weight increase of the polycondensate to finish and the molecular weight distribution to stabilize; more specifically, it ranges from several hours to several days. After the polycondensation reaction is complete, the resulting reactive silsesquioxane compound is preferably recovered by any method such as filtration or solvent removal, and purified as necessary.

[0032] Furthermore, a reactive silsesquioxane compound (A) can also be obtained by polycondensing alkoxysilane compound A represented by formula [1] and alkoxysilane compound B represented by formula [2] in the presence of a base, and then removing the base using a cation exchange resin. The above-mentioned base and its amount used may be one or more compounds selected from the group consisting of the basic compounds and fluoride salts described above, and the amount used may be such that, preferably, one or more compounds selected from the group consisting of potassium hydroxide, calcium hydroxide, barium hydroxide, and tetraethylammonium hydroxide can be used as the base. Furthermore, the reaction conditions and reaction solvents used in the polycondensation reaction can be those described above. After the reaction is complete, an ion exchange resin having a sulfo group as an ionic group is preferably used as the cation exchange resin for removing the base.

[0033] The polycondensate obtained by such a reaction ((A) reactive silsesquioxane compound) has a weight-average molecular weight Mw of 500 to 100,000, preferably 500 to 30,000, as measured in polystyrene equivalent by GPC, and a dispersion degree: Mw (weight-average molecular weight) / Mn (number-average molecular weight) of 1.0 to 10. Furthermore, the above (A) reactive silsesquioxane compound is [Ar 1 SiO 3 / 2 ] and [Ar 2 SiO 3 / 2 It is a cross-linked compound having at least one siloxane unit represented by ].

[0034] <(B) Fluorene compound> The (B) fluorene compound used in the core-forming composition is a compound represented by formula [3]. [ka] In the above formula [3], R 3 and R 4 Each of these independently represents a hydrogen atom or a methyl group, L 1 and L 2 Each of these independently represents an optionally substituted phenylene group or an optionally substituted naphthalenediyl group, L 3 and L 4 Each of these independently represents an alkylene group having 1 to 6 carbon atoms, and m and n represent 0 or a positive integer such that m+n is between 0 and 40.

[0035] L 1 and L 2 Examples of phenylene groups that may have substituents represented by include o-phenylene group, m-phenylene group, p-phenylene group, 2-methylbenzene-1,4-diyl group, 2-aminobenzene-1,4-diyl group, and 2,4-dibromobenzene-1,3-diyl group. Examples include yl groups and 2,6-dibromobenzene-1,4-diyl groups. Also, L 1 and L 2 Examples of naphthalenediyl groups that may have substituents represented by include 1,2-naphthalenediyl, 1,4-naphthalenediyl, 1,5-naphthalenediyl, 1,8-naphthalenediyl, 2,3-naphthalenediyl, and 2,6-naphthalenediyl groups.

[0036] L 3 and L 4Examples of alkylene groups with 1 to 6 carbon atoms represented by include methylene group, ethylene group, trimethylene group, 1-methylethylene group, tetramethylene group, 1-methyltrimethylene group, 1,1-dimethylethylene group, pentamethylene group, 1-methyltetramethylene group, 2-methyltetramethylene group, 1,1-dimethyltrimethylene group, 1,2-dimethyltrimethylene group, 2,2-dimethyltrimethylene group, 1-ethyltrimethylene group, hexa Examples include methylene group, 1-methylpentamethylene group, 2-methylpentamethylene group, 3-methylpentamethylene group, 1,1-dimethyltetramethylene group, 1,2-dimethyltetramethylene group, 2,2-dimethyltetramethylene group, 1-ethyltetramethylene group, 1,1,2-trimethyltrimethylene group, 1,2,2-trimethyltrimethylene group, 1-ethyl-1-methyltrimethylene group, and 1-ethyl-2-methyltrimethylene group.

[0037] In the compound represented by formula [3], m and n are preferably such that m+n is between 0 and 30, and more preferably such that m+n is between 2 and 20.

[0038] Specific examples of compounds represented by the above formula [3] include, for example, 9,9-bis(4-(2-(meth)acryloyloxyethoxy)phenyl)-9H-fluorene, Ogusol® EA-0200, EA-0300, EA-F5003, EA-F5503, EA-F5510, EA-F5710, GA-5000 [all manufactured by Osaka Gas Chemical Co., Ltd.], NK ester A-BPEF [manufactured by Shin Nakamura Chemical Industry Co., Ltd.], etc., but are not limited to these (in this specification, the (meth)acryloyl group refers to both the acryloyl group and the methacryloyl group).

[0039] In the core-forming composition, the content of component (B) is 10 to 500 parts by mass per 100 parts by mass of component (A), with 30 to 250 parts by mass being preferred.

[0040] <(C) (meth)acrylate compounds that do not belong to the fluorene compounds (B) mentioned above> The core-forming composition may further contain, as component (C), a (meth)acrylate compound that does not belong to the (B) fluorene compound. In this specification, (meth)acrylate refers to both acrylate and methacrylate. In particular, it is preferable that component (C) contains at least an aromatic ring-containing (meth)acrylate compound, or at least a mono(meth)acrylate compound.

[0041] Examples of such (C) component (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 1-phenylethyl (meth)acrylate, 2-phenylethyl (meth)acrylate, 1-naphthyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, 9-anthryl (meth)acrylate, 9-anthrylmethyl Mono(meth)acrylate compounds such as ethyl(meth)acrylate, 9-phenanthryl(meth)acrylate, 9-phenanthrylmethyl(meth)acrylate, 1-phenoxyethyl(meth)acrylate, 2-phenoxyethyl(meth)acrylate, 2-phenoxybenzyl(meth)acrylate, 3-phenoxybenzyl(meth)acrylate, 4-phenoxybenzyl(meth)acrylate, 2-(2-biphenylyloxy)ethyl(meth)acrylate, 2-(3-biphenylyloxy)ethyl(meth)acrylate, 2-(4-biphenylyloxy)ethyl(meth)acrylate, ethylene oxide-modified o-phenylphenol(meth)acrylate; neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate Examples include polyfunctional (meth)acrylate compounds such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bisphenol A di(meth)acrylate, ethylene oxide-modified bisphenol A di(meth)acrylate, 2-(5-ethyl-5-hydroxymethyl-1,3-dioxan-2-yl)-2-methylpropan-1-ol=di(meth)acrylate, ethylene oxide-modified 2-(5-ethyl-5-hydroxymethyl-1,3-dioxan-2-yl)-2-methylpropan-1-ol=di(meth)acrylate, and propylene oxide-modified 2-(5-ethyl-5-hydroxymethyl-1,3-dioxan-2-yl)-2-methylpropan-1-ol=di(meth)acrylate.

[0042] Among these, the (C) component is preferably benzyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-phenoxybenzyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, 4-phenoxybenzyl (meth)acrylate, 2-(2-biphenylyloxy)ethyl (meth)acrylate, 2-(3-biphenylyloxy)ethyl (meth)acrylate, 2-(4-biphenylyloxy)ethyl (meth)acrylate, and ethylene oxide-modified o-phenylphenol (meth)acrylate; more preferably benzyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, 2-(2-biphenylyloxy)ethyl (meth)acrylate, and ethylene oxide-modified o-phenylphenol (meth)acrylate; and even more preferably benzyl (meth)acrylate. Furthermore, 2-(5-ethyl-5-hydroxymethyl-1,3-dioxan-2-yl)-2-methylpropan-1-ol=di(meth)acrylate is preferred.

[0043] Furthermore, these (meth)acrylate compounds are readily available as commercial products, for example, HEA, HPA, 4-HBA, AIB, TBA, Viscoat 3F, 4F, 8F, 8FM, #295, #300, #802, #160, #192, #700HV, #540 [all manufactured by Osaka Organic Chemical Industry Co., Ltd.]; Light Acrylate NP-A, TMP-A, PE-3A, PE-4A, DPE-6A, PO-A, P2H-A, P-200A, BA-104, BP-4EAL, BP-4PA, Light Ester E, NB, IB, TB, M-3F, HOA(N), HO-250(N), HOP(N), HOP-A(N), HOB(N), NP, TMP, BZ, PO, BP-2EMK [all manufactured by Kyoeisha Chemical Co., Ltd.]; NK S Tel NPG, A-TMM-3, A-TMM-3L, A-TMM-3LM-N, A-TMPT, TMPT, A-TMMT, AD-TMP, A-9550, A-DPH, AMP-20 GY, PHE-1G, A-LEN-10, ABE-300, A-BPE-4, A-BPE-10, A-BPE-20, A-BPE-30, A-BPP-3, A-B1206PE, BPE-80N, BPE-100, BPE-200, BPE-500, BPE-900, BPE-1300N, A-9300, A-9300S, A-9300-1CL, A-DOG [all manufactured by Shin Nakamura Chemical Industry Co., Ltd.]; Arronix (registered trademark) M-309, M-306, M-305, M-303, M-452, M-450, M-408, M-403, M- 400, M-402, M-404, M-406, M-405, M-101A, M-102, M-106, M-110, M-111, M -113, M-117, M-5700, M-208, M-211B, M-215, M-313, M-315 [all manufactured by Toagosei Co., Ltd. ];Blenmar (registered trademark) AAE-300, PAE-100, 43PAPE-600B, ANP-300, 75ANEP-600, PDBE-200, PDBE-250, PDBE-450, PDBE-1300, PDBPE [manufactured by NOF Corporation];KAYARAD Examples include NPGDA, TMPTA, PET-30, T-1420(T), D-310, DPHA, DPCA-20, DPCA-30, DPCA-60, DPCA-120, R-128H, R-551, and R-712 [all manufactured by Nippon Kayaku Co., Ltd.].

[0044] (C) When adding a (meth)acrylate compound that does not belong to the fluorene compound (B) above, the (meth)acrylate compound may be used alone or in a mixture of two or more types. The amount added can be 1 to 50 parts by mass per 100 parts by mass of the total amount of component (A) and component (B), for example, 10 to 40 parts by mass or 15 to 40 parts by mass.

[0045] <Other additives> The core-forming composition may contain, as is appropriate, components (A) and (B), and component (C) as needed, polymerization initiators, chain transfer agents, antioxidants, ultraviolet absorbers, light stabilizers, leveling agents, rheology modifiers, adhesion aids such as silane coupling agents, pigments, dyes, and defoaming agents, provided that the effects of the present invention are not impaired. It may also further contain other polymerizable compounds.

[0046] Either a photopolymerization initiator or a thermal polymerization initiator can be used as the polymerization initiator mentioned above. Examples of photopolymerization initiators include alkylphenones, benzophenones, acylphosphine oxides, Michler's benzoylbenzoates, oxime esters, tetramethylthiuram monosulfides, and thioxanthones. In particular, photocleavage-type photoradical polymerization initiators are preferred. Examples of photocleavage-type photoradical polymerization initiators include those described in "Latest UV Curing Technology" (page 159, author: Kazuhiro Takasuki, publisher: Technical Information Association Co., Ltd., published in 1991). Examples of commercially available photoradical polymerization initiators include OMNIRAD® (formerly IRGACURE®) 184, 369, 651, 500, 819, 907, 784, 2959, CGI1700, CGI1750, CGI1850, CG24-61, TPO, Darocur® 1116, 1173 [all from IGM Group BV], ESACURE KIP150, KIP65LT, KIP100F, KT37, KT55, KTO46, KIP75 [all from Lamberti].

[0047] Examples of thermal polymerization initiators include azo compounds and organic peroxides. Examples of commercially available azo-based thermal polymerization initiators include V-30, V-40, V-59, V-60, V-65, and V-70 [all manufactured by Fujifilm Wako Pure Chemical Corporation (formerly Wako Pure Chemical Industries, Ltd.)]. Examples of commercially available organic peroxide-based thermal polymerization initiators include, but are not limited to, Percadox® CH, BC-FF, 14, 16, Trigonox® 22, 23, 121, Kayaester® P, O, Kayabutyl® B [all manufactured by Kayaku Akzo Co., Ltd.], Perhexa® HC, Permil® H, Perocta® O, Perhexyl® O, Z, Perbutyl® O, Z [all manufactured by NOF Corporation].

[0048] When a polymerization initiator is added, it may be used alone or in a mixture of two or more. The amount added is 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, per 100 parts by mass of the total amount of polymerizable components, i.e., components (A) and (B) above, and if component (C) is included, per 100 parts by mass of the total amount of components (A) to (C).

[0049] Examples of the above-mentioned chain transfer agents include thiol compounds such as methyl mercaptoacetate, methyl 3-mercaptopropionate, 2-ethylhexyl 3-mercaptopropionate, 3-methoxybutyl 3-mercaptopropionate, n-octyl 3-mercaptopropionate, stearyl 3-mercaptopropionate, 1,4-bis(3-mercaptopropionyloxy)butane, 1,4-bis(3-mercaptobutyryloxy)butane, and trimethylol. Ethantrys (3-mercaptopropionate), trimethylolethantrys (3-mercaptobutyrate), trimethylolpropantrys (3-mercaptopropionate), trimethylolpropantrys (3-mercaptobutyrate), pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-mercaptobutyrate), dipentaerythritol hexakis (3-mercaptopropionate) Mercaptocarboxylic acid esters such as tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate, tris[2-(3-mercaptobutyryloxy)ethyl]isocyanurate, etc.; ethanethiol, 2-methylpropane-2-thiol, n-dodecanethiol, 2,3,3,4,4,5-hexamethylhexane-2-thiol (tert-dodecanethiol) Alkyl thiols such as ethanol, ethane-1,2-dithiol, propane-1,3-dithiol, and benzylthiol; aromatic thiols such as benzenethiol, 3-methylbenzenethiol, 4-methylbenzenethiol, naphthalene-2-thiol, pyridine-2-thiol, benzimidazole-2-thiol, and benzothiazole-2-thiol; mercaptoalcohols such as 2-mercaptoethanol and 4-mercapto-1-butanol;Silane-containing thiols such as 3-(trimethoxysilyl)propane-1-thiol and 3-(triethoxysilyl)propane-1-thiol: Disulfide compounds include diethyl disulfide, dipropyl disulfide, diisopropyl disulfide, dibutyl disulfide, di-tert-butyl disulfide, dipentyl disulfide, diisopentyl disulfide, dihexyl disulfide, dicyclohexyl disulfide, didecyl disulfide, bis(2,3,3,4,4,5-hexamethylhexane-2-yl) disulfide (di-tert-dodecyl disulfide), bis(2,2-diethoxy Examples include alkyl disulfides such as ethyl disulfide, bis(2-hydroxyethyl) disulfide, and dibenzyl disulfide; aromatic disulfides such as diphenyl disulfide, di-p-tolyl disulfide, di(pyridine-2-yl)pyridyl disulfide, di(benzimidazole-2-yl) disulfide, and di(benzothiazole-2-yl) disulfide; thiuram disulfides such as tetramethyl thiuram disulfide, tetraethyl thiuram disulfide, tetrabutyl thiuram disulfide, and bis(pentamethylene) thiuram disulfide; and α-methylstyrene dimers.

[0050] When a chain transfer agent is added, it may be used alone or in a mixture of two or more types. The amount to be added is 0.01 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the total amount of polymerizable components, i.e., components (A) and (B) above, and if component (C) is included, per 100 parts by mass of the total amount of components (A) to (C).

[0051] Examples of the above-mentioned antioxidants include phenolic antioxidants, phosphoric acid-based antioxidants, and sulfide-based antioxidants, but phenolic antioxidants are preferred among them. Examples of phenolic antioxidants include IRGANOX® 245 and 1. Examples include 010, 1035, 1076, and 1135 [all manufactured by BASF Japan Ltd.], Sumirizer® GA-80, GP, MDP-S, BBM-S, and WX-R [all manufactured by Sumitomo Chemical Co., Ltd.], and Adeka Stab® AO-20, AO-30, AO-40, AO-50, AO-60, AO-80, and AO-330 [all manufactured by ADEKA Corporation].

[0052] When an antioxidant is added, it may be used alone or in a mixture of two or more types. The amount added is 0.01 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the total amount of polymerizable components, i.e., components (A) and (B) above, and if component (C) is included, per 100 parts by mass of the total amount of components (A) to (C).

[0053] <Composition for core formation> The method for preparing the core-forming composition is not particularly limited. For example, it can be prepared by mixing the aforementioned components (A) and (B), and optionally component (C) in a predetermined ratio, and further adding and mixing other additives as desired to obtain a homogeneous solution; by mixing at least a portion of at least two of these components, for example, components (A) to (C), to obtain a homogeneous solution, then adding the remaining components, further adding and mixing other additives as desired to obtain a homogeneous solution; or by using a conventional solvent in addition to these components. When using solvents, there are no particular restrictions as long as they are organic solvents commonly used in the relevant art. However, it is advisable to avoid using extremely polar or low polar solvents, such as water or hydrocarbon solvents like hexane, as this may lead to precipitate formation or phase separation. Furthermore, caution is required as adding large amounts of solvent may prevent the formation of a sufficient film thickness during film formation. When using a solvent, the proportion of solids in the core-forming composition is not particularly limited as long as each component is uniformly dissolved in the solvent, but for example, it may be 1 to 90% by mass, or 1 to 50% by mass, or 1 to 35% by mass. Here, solids refer to the total components of the core-forming composition excluding the solvent components. Furthermore, it is preferable to filter the core-forming composition using a filter with a pore size of 0.05 to 5 μm before using it to fabricate the optical waveguide described later.

[0054] [Composition for cladding] The cladding in the optical waveguide of the present invention is, for example, a cured product of a cladding composition comprising (D) a fluorene skeleton-containing epoxy compound and (G) a photoacid generator.

[0055] <(D) Fluorene skeleton-containing epoxy compound> The (D) fluorene skeleton-containing epoxy compound used in cladding compositions is a compound represented by the following formula [4]. [ka] In the above formula [4], L 5 and L 6 Each of the following independently represents a naphthalenediyl group which may have substituents, and each of the following independently represents an integer from 0 to 10.

[0056] L 5 and L 6 In this, substituents on the naphthalenediyl group (on the naphthalene ring) include methyl Examples include alkyl groups having 1 to 6 carbon atoms, such as propyl, isopropyl, butyl, and t-butyl groups. Also L 5 and L 6 The number of substituents on the naphthalenediyl group in is independently 0 to 6, preferably 0 to 2, more preferably 0 or 1, and most preferably 0. Note L 5 and L 6The types of substituents in the compound may be the same or different. If there are two or more substituents on the same naphthalene ring, they may be the same or different.

[0057] (D) Specific examples of epoxy compounds containing a fluorene skeleton include compounds represented by the following formula [4a]. [ka]

[0058] The above (D) fluorene skeleton-containing epoxy compound can be a commercially available product. Examples include Ogusol® CG-500 and EG-280 (manufactured by Osaka Gas Chemical Co., Ltd.). Such epoxy compounds containing a fluorene skeleton having a naphthalene ring can be used individually or in combination of two or more. Furthermore, from the viewpoint of solubility of the resin component and refractive index, for example, the above-mentioned Ogusol® CG-500 can be used alone.

[0059] When the above cladding composition contains the <other epoxy compounds> described later, the amount of (D) fluorene skeleton-containing epoxy compound can be, for example, 5 to 50 parts by mass, or 10 to 40 parts by mass, relative to the total amount of epoxy compounds (100 parts by mass total of (D) fluorene skeleton-containing epoxy compound and <other epoxy compounds>). In this specification, the epoxy compound of component (D) and the <other epoxy compounds> described later are also referred to as "resin components". By using (D) fluorene skeleton-containing epoxy compound together with <other epoxy compounds>, ​​and by using the amount of (D) fluorene skeleton-containing epoxy compound at 5 parts by mass or more, a sufficient refractive index can be obtained as a cladding material. Furthermore, by using the amount at 50 parts by mass or less, deterioration of storage stability due to precipitation is less likely to occur in the cladding composition, and a decrease in film-forming properties is also less likely to occur, making this a preferred embodiment.

[0060] <Other epoxy compounds> The cladding composition described above may include, in addition to the (D) fluorene skeleton-containing epoxy compound, <other epoxy compounds>.

[0061] [(E) Monofunctional or bifunctional alicyclic epoxy compounds] As the above <other epoxy compounds>, ​​(E) monofunctional or difunctional alicyclic epoxy compounds can be used. The monofunctional or difunctional alicyclic epoxy compound that is component (E) is not particularly limited as long as it is a compound having one or two alicyclic epoxy groups. For example, the above (E) alicyclic epoxy compound may be in liquid form, and may also have patterning properties (exposure sensitivity). From the perspective of degree, it can be a compound having two epoxy groups introduced into an alicyclic skeleton. In this specification, "monofunctional or difunctional" means containing one or two epoxy groups as functional groups.

[0062] Examples of the above (E) alicyclic epoxy compounds include compounds represented by the following formula [5]. [ka] In formula [5], R 5 and R 6 Each of these independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, which may have a hydrogen atom, an ester group, or an ether group, or a cyclic alkyl group having 3 to 6 carbon atoms, or a combination of the linear or branched alkyl group and the cyclic alkyl group, in which case the linear alkyl group having 2 or more carbon atoms, the branched alkyl group having 3 or more carbon atoms, or the cyclic alkyl group may form an epoxy ring together with adjacent carbon atoms, or R 5 and R 6 These atoms may bond to each other to form a ring with 4 to 6 carbon atoms, and in this case, they may combine with adjacent carbon atoms constituting the ring to form an epoxy ring.

[0063] Examples of linear or branched alkyl groups having 1 to 6 carbon atoms include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, 1-methylbutyl group, 2-methylbutyl group, 3-methylbutyl group, 1,1-dimethylpropyl group, 1,2-dimethylpropyl group, 2,2-dimethylpropyl group, 1-ethylpropyl group, n-hexyl group, 1-methylpentyl group, 2-methylpentyl group, 3-methylpentyl group, 4-methylpentyl group, 1,1-dimethylbutyl group, 1,2-dimethylbutyl group, 1,3-dimethylbutyl group, 2,2-dimethylbutyl group, 2,3-dimethylbutyl group, 3,3-dimethylbutyl group, 1-ethylbutyl group, 2-ethylbutyl group, 1,1,2-trimethylpropyl group, 1,2,2-trimethylpropyl group, 1-ethyl-1-methylpropyl group, and 1-ethyl-2-methylpropyl group. Examples of cyclic alkyl groups having 3 to 6 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl groups.

[0064] In a preferred embodiment, the above (E) alicyclic epoxy compound can be a compound represented by the following formulas [5a], [5b], and [5c]. These compounds have low molecular weights and are liquid compounds, making them suitable not only from the viewpoint of patterning properties but also from the viewpoint of adjusting the viscosity of the composition. [ka]

[0065] The above (E) alicyclic epoxy compound can be a commercially available product. (E) Examples of commercially available difunctional alicyclic epoxy compounds in component (E) include diepoxybicyclohexyl (e.g., Celoxide® 8000, 8010, manufactured by Daicel Corporation) and 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl Examples include xene carboxylate (e.g., Celoxide® 2021P, manufactured by Daicel Corporation), epsilon-caprolactone-modified 3,4-epoxycyclohexylmethyl 3',4'-epoxycyclohexane carboxylate (e.g., Celoxide® 2081, manufactured by Daicel Corporation), bis(3,4-epoxycyclohexylmethyl) adipate, and diepoxylated tetrahydroindene (e.g., Epocalic® THI-DE, manufactured by ENEOS Corporation). Furthermore, as monofunctional alicyclic epoxy compounds, for example, 3,4-epoxycyclohexylmethyl methacrylate (e.g., Cyclomer® M-100, manufactured by Daicel Corporation), 3,4-epoxycyclohexylmethyl methacrylate, 1,2-epoxy-4-vinylcyclohexane (e.g., Celoxide® 2000, manufactured by Daicel Corporation), and 1,2,8,9-diepoxylimonene (e.g., Celoxide® 3000, manufactured by Daicel Corporation) can be used.

[0066] (E) When using an alicyclic epoxy compound, the amount added can be, for example, 10 to 80 parts by mass, or 20 to 70 parts by mass, relative to the total amount of epoxy compounds ((D) fluorene skeleton-containing epoxy compound and <other epoxy compounds> totaling 100 parts by mass). Adding 20 parts by mass or more of the (E) alicyclic epoxy compound makes it easier to obtain sufficient patterning properties, while adding 80 parts by mass or less makes it easier to obtain a sufficient refractive index.

[0067] [(F) Monofunctional or bifunctional aromatic epoxy compounds] As the above-mentioned <other epoxy compounds>, ​​(F) monofunctional or bifunctional aromatic epoxy compounds can be used. Here, component (F) is a different compound from the (D) fluorene skeleton-containing epoxy compound represented by formula [4] above. (F) From the viewpoint of patternability (exposure sensitivity), aromatic epoxy compounds can be compounds having two epoxy groups in a preferred embodiment. In particular, epoxy compounds having a bisphenol A type skeleton or a bisphenol F type skeleton can be preferably used as component (F).

[0068] (F) Commercial aromatic epoxy compounds can be used. Examples of difunctional aromatic epoxy compounds in component (F) include jER(registered trademark) 806, a bisphenol F type epoxy compound manufactured by Mitsubishi Chemical Corporation, and jER(registered trademark) 828, a bisphenol A type epoxy compound manufactured by Mitsubishi Chemical Corporation. Other examples of monofunctional aromatic epoxy compounds include phenyl glycidyl ether (e.g., Denacol® EX-141, manufactured by Nagase ChemteX Corporation), phenol (EO) 5 glycidyl ether (e.g., Denacol® EX-145, manufactured by Nagase ChemteX Corporation), and p-tert-butylphenyl glycidyl ether (e.g., Denacol® EX-146, manufactured by Nagase ChemteX Corporation).

[0069] (F) When using aromatic epoxy compounds, the amount added can be, for example, 5 to 60 parts by mass, or 10 to 50 parts by mass, relative to the total amount of epoxy compounds ((D) fluorene skeleton-containing epoxy compounds and <other epoxy compounds> total of 100 parts by mass). (F) Adding aromatic epoxy compounds in amounts of 5 parts by mass or more makes it easier to obtain a sufficient refractive index and a uniform film, while adding them in amounts of 60 parts by mass or less makes it easier to obtain sufficient patternability.

[0070] [Other epoxy compounds] Furthermore, the cladding composition may contain, to the extent that it does not impair the effects of the present invention, (D) a fluorene skeleton-containing epoxy compound, and also (E) an alicyclic epoxy compound, and (F) Other epoxy compounds besides aromatic epoxy compounds may be included as "<other epoxy compounds>". Examples of such epoxy compounds include heterocyclic epoxy compounds such as triglycidyl isocyanurates, aliphatic epoxy compounds, and alkoxysilanes having epoxy groups. Specific examples of the above aliphatic epoxy compounds include monofunctional epoxy compounds such as glycidyl ethers of aliphatic alcohols and glycidyl esters of alkyl carboxylic acids, as well as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts. Representative specific compounds include monoalcohol glycidyl ethers such as allyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and C12-13 mixed alcohol glycidyl ether; 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol tetraglycidyl ether, dipentaerythritol hexaglycidyl ether, and polyethylene glycol diglycidyl ether. Examples include glycidyl ethers of polyhydric alcohols such as diglycidyl ether of polypropylene glycol; polyglycidyl ether derivatives of polyether polyols, which are alkylene oxide adducts of one or more aliphatic polyhydric alcohols such as propylene glycol, trimethylolpropane, and glycerin; and alkoxysilanes having epoxy groups such as 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane. Such epoxy compounds can be included, for example, in a proportion of 0 to 20 parts by mass relative to the total amount of epoxy compounds (100 parts by mass of the total amount of (D) fluorene skeleton-containing epoxy compounds and <other epoxy compounds>).

[0071] [(G) Photoacid Generator] Specific examples of (G) photoacid generators used in cladding compositions include onium salts such as iodonium salts, sulfonium salts, phosphonium salts, and selenium salts, metallocene complex compounds, iron arene complex compounds, disulfone compounds, sulfonic acid derivative compounds, triazine compounds, acetophenone derivative compounds, and diazomethane compounds.

[0072] Among the above onium salts, iodonium salts include, for example, diarylliodonium salts such as chlorides, bromides, mesylates, tosylates, trifluoromethanesulfonates, tetrafluoroborates, tetrakis(pentafluorophenyl)borates, hexafluorophosphates, hexafluoroarsenates, and hexafluoroantimonates, which are diarylliodonium salts such as diphenyliodonium, 4,4'-dichlorodiphenyliodonium, 4,4'-dimethoxydiphenyliodonium, 4,4'-di-tert-butyldiphenyliodonium, 4-methylphenyl(4-(2-methylpropyl)phenyl)iodonium, 3,3'-dinitrophenyliodonium, 4-(1-ethoxycarbonylethoxy)phenyl(2,4,6-trimethylphenyl)iodonium, and 4-methoxyphenyl(phenyl)iodonium.

[0073] Examples of the above sulfonium salts include triphenylsulfonium, diphenyl(4-tert-butylphenyl)sulfonium, tris(4-tert-butylphenyl)sulfonium, diphenyl(4-methoxyphenyl)sulfonium, tris(4-methylphenyl)sulfonium, tris(4-methoxyphenyl)sulfonium, tris(4-ethoxyphenyl)sulfonium, diphenyl(4-(phenylthio)phenyl)sulfonium, tris(4-(phenylthio)phenyl)sulfonium, and other triarylsulfonium salts. Examples of triarylsulfonium salts include chlorides, bromides, trifluoromethanesulfonates, tetrafluoroborates, hexafluorophosphates, hexafluoroarcenates, hexafluoroantimonates, and tetrakis(pentafluorophenyl)gallates.

[0074] Examples of the phosphonium salts mentioned above include arylphosphonium salts such as chlorides, bromides, tetrafluoroborates, hexafluorophosphates, and hexafluoroantimonates of triarylphosphoniums or tetraarylphosphoniums, such as tetraphenylphosphonium, ethyltriphenylphosphonium, tetra(p-methoxyphenyl)phosphonium, ethyltri(p-methoxyphenyl)phosphonium, and benzyltriphenylphosphonium.

[0075] Examples of the selenium salts mentioned above include triarylselenium salts such as triphenylselenium hexafluorophosphate.

[0076] Examples of the iron arene complex compounds mentioned above include bis(η5-cyclopentadienyl)(η6-isopropylbenzene)iron(II)hexafluorophosphate.

[0077] Among these, iodonium salts, sulfonium salts, etc., can be suitably used as photoacid generators. Commercially available products can be used, and examples include triarylsulfonium salts such as CPI-310FG and CPI-101A [both manufactured by Sunapro Co., Ltd.].

[0078] (G) Photoacid generators can be used alone or in combination of two or more types. (G) The photoacid generator can usually be added in an amount of, for example, 0.1 to 10 parts by mass, or 0.2 to 5 parts by mass, relative to 100 parts by mass of the total mass of the resin components, i.e., 100 parts by mass of the total mass of the (D) fluorene skeleton-containing epoxy compound and optionally the other epoxy compound. If the amount of (G) photoacid generator added is less than 0.1 parts by mass, the photocuring reaction may not proceed sufficiently. If it exceeds 10 parts by mass, the degree of polymerization of the polymer will decrease, and it may become brittle and prone to cracking.

[0079] <Other additives> The cladding composition may contain, as necessary, components (D) and (G) above, and additionally, components (E) and (F) and other epoxy compounds, as long as the effects of the present invention are not impaired, anti-reflective agents, ultraviolet absorbers, antioxidants, light stabilizers, sensitizers, surfactants, crosslinking agents, leveling agents, silane coupling agents, and the like. When these other additives are used, they can usually be blended in a proportion of 10 parts by mass or less per 100 parts by mass of the total mass of the resin components ((D) fluorene skeleton-containing epoxy compound, and optionally <other epoxy compounds>).

[0080] <Composition for cladding> The method for preparing the cladding composition is not particularly limited. Examples include adding and mixing the aforementioned components (D) and (G), optionally other epoxy compounds (such as components (E) and (F)), and optionally other additives to obtain a homogeneous solution, or using conventional organic solvents in addition to these components. When the prepared cladding composition has low viscosity, good film formation is possible without adding organic solvents. In this case, since it is solvent-free, it is advantageous that there is no need for a process to volatilize the organic solvent by heat treatment or other means after film formation. Furthermore, by not including organic solvents, there is no risk of health damage to workers from inhalation during the volatilization of organic solvents, or damage to surrounding equipment. Concerns about corrosion and other issues are significantly reduced. Since the cladding composition is a relatively low-viscosity composition, the inclusion of organic solvents is not essential, but even if organic solvents are included, the above-mentioned effects of the present invention will not be lost, and they can be added in any proportion. There are no particular restrictions on the organic solvents that can be used in the cladding composition as long as they are organic solvents commonly used in the art, however, it is desirable to refrain from using extremely polar or low polar solvents, such as water or hydrocarbon solvents like hexane, as this may cause precipitate formation or phase separation. In addition, care should be taken as adding a large amount of organic solvent may prevent sufficient film thickness from being achieved during film formation. When using an organic solvent, the proportion of solids in the cladding composition is not particularly limited as long as each component is uniformly dissolved in the organic solvent, but is, for example, 60% by mass or more, or 70% by mass or more. Preferably, the proportion of solids in the composition can be, for example, 75% by mass to 100% by mass. Here, solids refer to the total components of the cladding composition excluding the organic solvent components. Furthermore, it is preferable to filter the cladding composition using a filter with a pore size of 0.05 to 5 μm before using it to fabricate the optical waveguide described later.

[0081] Furthermore, the cladding composition preferably has a viscosity that allows for excellent workability in the formation of optical waveguides. For example, the viscosity of the above-mentioned optical cladding composition can be 100 to 10,000 mPa·s at 25°C.

[0082] [Manufacturing method for optical waveguides] The optical waveguide of the present invention can be manufactured by a manufacturing method including, for example, the first to fourth steps shown in (1) to (4) below. (1) The first step of forming the lower cladding, (2) A second step of forming a patterned core on the lower cladding, (3) A third step of forming the upper cladding so as to join it with the lower cladding and cover the core, (4) A fourth step of forming a protective layer on the necessary outer surface portion of the upper cladding or lower cladding.

[0083] (1) First step The first step is to form a lower cladding made of a cured product of the cladding composition, for example, using the cladding composition described above. In this process, for example, the aforementioned cladding composition is applied to a substrate and dried to obtain a coating film, and the lower cladding, which is a cured product, is obtained by exposing (photocuring) the coating film. Specifically, first, the aforementioned cladding composition (which, if necessary, is dissolved or dispersed in an organic solvent to form a varnish (film-forming material)) is applied and dried onto a suitable substrate using coating methods such as spin coating, blade coating, dip coating, roll coating, bar coating, die coating, inkjet printing, and printing (relief printing, flat printing, screen printing, etc.) to form a coating film. The substrate forming the lower cladding is not particularly limited, but one with excellent flatness is preferred. Examples include metal substrates, silicon substrates, and transparent substrates, which can be appropriately selected depending on the optical waveguide configuration. Preferred examples of metal substrates include gold, silver, copper, platinum, aluminum, and chromium, while preferred examples of transparent substrates include glass and plastic (polyethylene terephthalate, etc.). When a lower electrode is placed between the substrate and the lower cladding, known electrodes can be used. The lower electrode may be a metal vapor-deposited layer or a transparent electrode layer. Preferred examples of metals to be vapor-deposited include gold, silver, copper, platinum, aluminum, and chromium. Preferred examples of transparent electrode layers include indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and antimond-doped tin oxide. Examples include The drying method for the coating film is not particularly limited; for example, it can be done using a hot plate or oven under appropriate conditions, such as air, an inert gas like nitrogen, or a vacuum. The drying temperature is not particularly limited, but is, for example, 40 to 250°C. Examples of light rays used to expose the coating film include ultraviolet rays, electron beams, and X-rays. Light sources that can be used for ultraviolet irradiation include sunlight, chemical lamps, low-pressure mercury lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, and UV-LEDs. Furthermore, post-baking may be performed after exposure to stabilize the physical properties of the cured material. The method of post-baking is not particularly limited, but it is usually carried out using a hot plate, oven, etc., at a temperature of 50 to 260°C for 1 to 120 minutes.

[0084] (2)Second process The second step is to form a patterned core on the lower cladding formed in the first step, for example, by photolithography of a coating of the aforementioned core-forming composition. This process involves, for example, applying the aforementioned core-forming composition onto the aforementioned lower cladding, then irradiating and developing it with ultraviolet light through a photomask to obtain a patterned core. Specifically, first, for example, the aforementioned core-forming composition (which, if necessary, is dissolved or dispersed in an organic solvent to form a varnish (film-forming material)) is applied to the lower cladding using the aforementioned coating method. Next, after irradiating with ultraviolet light through a photomask (after pattern exposure), development is performed using an organic solvent or an alkaline aqueous solution. Examples of developers include isopropyl alcohol, propylene glycol monomethyl ether, ethylamine aqueous solution, n-propylamine aqueous solution, diethylamine aqueous solution, di-n-propylamine aqueous solution, triethylamine aqueous solution, methyldiethylamine aqueous solution, diethanolamine aqueous solution, triethanolamine aqueous solution, tetramethylammonium hydroxide aqueous solution, sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, sodium silicate aqueous solution, and sodium metasilicate aqueous solution. Development dissolves and removes the composition in the unexposed areas. After development, post-baking may be performed as needed to stabilize the physical properties of the cured material. The method of post-baking is not particularly limited, but it is usually performed using a hot plate, oven, etc., at a temperature of 50 to 260°C for 1 to 120 minutes.

[0085] (3) Third step The third step is to form an upper cladding using, for example, the aforementioned cladding composition, so as to join it with the lower cladding and cover the core. This process can be carried out in the same manner as the first process (1) described above.

[0086] (4) 4th step The fourth step is to form a protective layer, preferably a metal oxide-containing layer, on the required outer surface portion of the upper cladding or lower cladding. In this process, methods for forming the protective metal oxide-containing layer include sputtering, laser ablation, and electron beam deposition. Among these, sputtering is preferred because it allows for the formation of the protective layer at low temperatures and does not damage the upper / lower cladding layers. The protective layer can have a thickness of, for example, 0.1 to 0.5 μm. The protective layer may also have a thickness of 0.5 μm or more, but even if the protective layer is 0.5 μm or more, it will not affect the change in propagation loss described later.

[0087] Furthermore, the optical waveguide of the present invention is a grade in which the refractive index of the core changes continuously with respect to the direction of motion. It can take any of the following forms: a groove index (GI) type, a multi-step index (MI) type in which the refractive index of the core changes stepwise with respect to the longitudinal direction, or a step index (SI) type in which the refractive index changes discontinuously only at the interface between the core and the cladding. [Examples]

[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The apparatus and conditions used for sample preparation and physical property analysis in the examples are as follows:

[0089] (1) Stirring and defoaming machine Equipment: Shinky Co., Ltd. Rotation / Revolution Mixer Awatori Rentaro (Registered Trademark) ARE-310 (2) UV exposure Equipment: Batch-type UV irradiation device manufactured by iGraphics Co., Ltd. (high-pressure mercury lamp 2kW x 1 lamp) (3) Mask aligner Equipment: Süss Microtec MA6 Lamp: High-pressure mercury lamp Filter: i-line bandpass filter Illuminance: 7mW / cm2 (365nm detection) (4) Dicing saw Device: DAD323 manufactured by DISCO Corporation (5) Automatic alignment device Equipment: Automatic centering device FCCB-253 manufactured by Sigma Koki Co., Ltd.

[0090] CG-500: Ogusol (registered trademark) CG-500, manufactured by Osaka Gas Chemical Co., Ltd. CEL-8010: Celoxide (registered trademark) 8010, manufactured by Daicel Chemicals, Ltd. jER806: Bisphenol F type epoxy resin, manufactured by Mitsubishi Chemical Corporation. M-100: Cyclomer (registered trademark) M-100 (3,4-epoxycyclohexylmethyl methacrylate), manufactured by Daicel Corporation. EX-141: Denacol® EX-141 (phenylglycidyl ether), manufactured by Nagase ChemteX Corporation. STMS: Trimethoxy(4-vinylphenyl)silane [manufactured by Shin-Etsu Chemical Co., Ltd.] PTMS: Trimethoxy(phenyl)silane [manufactured by Shin-Etsu Chemical Co., Ltd.] TEAH: 35% by mass aqueous solution of tetraethylammonium hydroxide [manufactured by Aldrich] FDA: Bisarylful Orange Acrylate [Ogusol® EA-F5503, manufactured by Osaka Gas Chemical Co., Ltd.] BnA: Benzyl acrylate [Manufactured by Osaka Organic Chemical Industry Co., Ltd., Viscoat #160] I1010: Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate][Manufactured by BASF Japan Ltd., IRGANOX® 1010] O819: Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide [Manufactured by BASF Japan Ltd., OMNIRAD® 819] CPI-310FG: Triarylsulfonium salt type photoacid generator, manufactured by Sunapro Co., Ltd. Tinuvin384-2: Benzotriazole-based UV absorber, manufactured by BASF Japan Ltd. UVS-1331: Sensitizer, manufactured by Kawasaki Chemical Industries, Ltd. IPA: Isopropyl alcohol PGMEA: Propylene glycol monomethyl ether acetate THF: Tetrahydrofuran KBM-403:3-Glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.

[0091] [1] Preparation of cladding / core forming materials [Example 1-1] Preparation of cladding composition 20 parts by mass of CG-500, 35 parts by mass of jER806, 5 parts by mass of M-100, 8 parts by mass of EX-141, and 32 parts by mass of CEL-8010 were mixed together. To this mixture, 1 part by mass of photoacid generator CPI-310FG, 0.5 parts by mass of KBM-403, 1 part by mass of Tinuvin384-2, and 0.2 parts by mass of UVS-1331 were added. The mixture was stirred under heating at 110°C or below to completely dissolve the solid components, thereby preparing a liquid cladding composition.

[0092] [Examples 1-2] Preparation of Core-Forming Composition Following the procedure described in WO2018 / 199305, 2.97 g (7.1 mmol) of TEAH, 9.52 g (528 mmol) of deionized water, and 90 g of THF were charged into a 200 mL reaction flask equipped with a condenser, and the air in the flask was replaced with nitrogen using a nitrogen balloon. A mixture of 39.6 g (177 mmol) of STMS and 35.0 g (177 mmol) of PTMS was added dropwise over 10 minutes, and the mixture was stirred at 40°C for 16 hours. Next, 7.9 g of cation exchange resin [Amberlist® 15JWET, Dow Chemical], which had been previously washed with THF, was added to the reaction mixture, and the mixture was stirred for 1 hour to stop the reaction. The mixture was then cooled to room temperature (approximately 23°C). After that, the cation exchange resin was filtered through a 0.2 μm pore size membrane filter and then washed with 15 g of ethyl acetate. To the combined filtrate and washing solution, 9.3 g of BnA was added and mixed uniformly. Subsequently, using a rotary evaporator, THF, ethyl acetate, residual water, and other volatile components were removed under reduced pressure to obtain a reactive silsesquioxane compound 1 (hereinafter sometimes abbreviated as SQ) / BnA solution. The weight-average molecular weight Mw of SQ1, measured in polystyrene equivalent by GPC, was 4,000, and the dispersion ratio: Mw (weight-average molecular weight) / Mn (number-average molecular weight) was 1.8. Furthermore, quantitative analysis of the obtained solution by GC revealed that the SQ content was 75% by mass and the BnA content was 25% by mass. As a mixture of a reactive silsesquioxane compound and a (meth)acrylate compound, 54.3 parts by mass of the above SQ / BnA solution (40.7 parts by mass of SQ, 13.6 parts by mass of BnA), 31.6 parts by mass of FDA as a fluorene compound, 14.1 parts by mass of BnA as a (meth)acrylate compound (27.7 parts by mass including the BnA contained in the above SQ / BnA solution), 0.25 parts by mass of I1010 as an antioxidant, and 2 parts by mass of O819 as a polymerization initiator were mixed, and 18 parts by mass of PGMEA was added, and the mixture was heated and stirred at 50°C for 8 hours. The core-forming composition was prepared by further stirring and degassing for 10 minutes.

[0093] [2] Fabrication of optical waveguides with SiO2 sputtered film [Example 2-1] Manufacturing of Optical Waveguide 1 A silicon substrate was prepared by applying a PGMEA-diluted KBM403 solution by spin coating (2,000 rpm x 30 seconds) and heating it on a 110°C hot plate for 10 minutes to ensure adhesion. On this silicon substrate, the cladding composition prepared in Example 1 was applied by spin coating (1,800 rpm x 60 seconds) and heated on a 60°C hot plate for 1 minute to obtain a coating film. This coating film was then exposed to 20 mW / cm² of UV irradiation using a batch-type UV irradiation device manufactured by I-Graphics Co., Ltd. 2 The lower cladding layer was formed by exposing the image for 50 seconds. Next, the core-forming composition prepared in Example 2 was applied to the lower cladding layer by spin coating (1,600 rpm × 60 seconds), and a mask aligner (mask width 15 μm) was used to generate 7 mW / cm². 2 The material was pattern-exposed for 143 seconds. The unexposed composition was washed with a PGMEA / IPA mixture (mass ratio 1:1), and then heated on a hot plate at 100°C for 2 minutes to obtain a linear core layer with dimensions of 12 μm width × 11 μm height × 7 cm length. The resulting core layer was then coated with the cladding material prepared in Example 1 by spin coating (1,000 rpm x 60 seconds), and heated on a 60°C hot plate for 1 minute. A coating film was obtained. This coating film was then subjected to 20 mW / cm² UV irradiation using a batch-type UV irradiation device manufactured by I-Graphics Co., Ltd. 2 The substrate was exposed to light for 50 seconds, and then heated on a 180°C hot plate for 20 minutes to form the upper cladding layer and obtain an optical waveguide substrate. Finally, a 100 nm thick SiO2 film was formed on the obtained optical waveguide substrate by sputtering, and an optical waveguide 1 with an SiO2 protective film was obtained.

[0094] [Example 2-2] Manufacturing of Optical Waveguide 2 In the same manner as in Example 2-1, an optical waveguide was fabricated, and then a 300 nm thick SiO2 film was formed on the optical waveguide substrate by sputtering to obtain an optical waveguide 2 with an SiO2 protective film.

[0095] [Comparative Example 2-1] Manufacturing of Optical Waveguide 3 Optical waveguide 3 was fabricated in the same manner as in Example 2-1, except that the sputtering deposition process was omitted.

[0096] Optical waveguides 1-3 obtained from Examples 2-1, 2-2, and Comparative Example 2-1 were cut to a waveguide length of 6 cm using a dicing saw (DISCO Corporation, product name "DAD323"), and the insertion loss at a wavelength of 1.31 μm was measured. The results are shown in Table 1.

[0097] [Table 1]

[0098] As shown in Table 1, no effect of SiO2 sputter deposition on insertion loss was observed.

[0099] [3] High heat resistance test Optical waveguides 1-3 obtained from Examples 2-1, 2-2, and Comparative Example 2-1 were cut to a waveguide length of 6 cm using a dicing saw (DISCO Corporation, product name "DAD323"), and then placed in a 150°C constant temperature test chamber. After approximately 250 hours, each waveguide was removed from the constant temperature test chamber, 0.25 cm was cut from both ends of the waveguide, and the insertion loss at a wavelength of 1.31 μm was measured. This procedure was repeated until 1000 hours. The measurement results of the insertion loss at each elapsed time (test time) during the 150°C constant temperature test are shown in Tables 2 and 3, and Figure 1.

[0100] [Table 2]

[0101] [Table 3]

[0102] In Comparative Example 2-1, optical waveguide 3 showed a significant increase in insertion loss as the test time progressed during the 150°C constant temperature test. In contrast, no increase in insertion loss was observed in optical waveguide 1 of Example 2-1 and optical waveguide 2 of Example 2-2, which were coated with a sputtered SiO2 film. Although the loss decreased slightly over time, this is thought to be due to the removal of 0.25 cm from the waveguide end face during the insertion loss evaluation. Thus, the result that the insertion loss remained almost constant in the waveguides of the examples can be attributed to the protective effect of the SiO2 sputtered film.

[0103] [4] Propagation loss evaluation For the optical waveguide obtained by the same procedure as in Comparative Example 2-1, propagation loss was measured before the high heat resistance test using the method described in JPCA standard (2008) 4.6.2.1 cutback method. The propagation loss at a wavelength of 1.31 μm was 0.31 dB / cm. Similarly, propagation loss measurements were performed using the cutback method on the optical waveguides of Example 2-1 and Comparative Example 2-1 after undergoing the high heat resistance test (constant temperature test at 150°C for 1000 hours) described above. The propagation loss at a wavelength of 1.31 μm was 0.32 dB / cm (Example 2-1) and 2.03 dB / cm (Comparative Example 2-1), respectively. The results showed that the propagation loss of the optical waveguide after the high heat resistance test at 150°C deteriorated significantly in Comparative Example 2-1, which lacked an SiO2 sputtered film (from 0.31 dB / cm to 2.03 dB / cm), while it remained almost unchanged in Example 2-1, which had an SiO2 sputtered film (from 0.31 dB / cm to 0.32 dB / cm, change rate: 3.2%).

Claims

1. An optical waveguide comprising a core, a cladding having a lower refractive index than the core that surrounds and covers the entire outer periphery thereof, and a protective layer on at least a portion of the outer surface of the cladding, An optical waveguide in which, in a high-temperature endurance test involving storage at 150°C for 1000 hours under atmospheric conditions, the propagation loss value of light with a wavelength of 1.31 μm after the test is less than 10% of the value before the test.

2. The optical waveguide according to claim 1, wherein the protective layer is a metal oxide-containing layer.

3. The optical waveguide according to claim 2, wherein the protective layer is a silicon dioxide-containing layer.

4. The aforementioned core, (A) A reactive silsesquioxane compound and (B) A fluorene compound are included in the cured core-forming composition. The (A) reactive silsesquioxane compound is a polycondensate of alkoxysilane compound A represented by the following formula [1] and alkoxysilane compound B represented by the following formula [2]. The optical waveguide according to claim 1, wherein the (B) fluorene compound is a compound represented by the following formula [3]. 【Chemistry 1】 (In the formula, Ar 1 R represents a phenyl group having at least one group having a polymerizable double bond, a naphthyl group having at least one group having a polymerizable double bond, or a biphenyl group having at least one group having a polymerizable double bond. 1 (This represents a methyl group or an ethyl group.) 【Chemistry 2】 (In the formula, Ar 2 R represents a phenyl group which may be substituted with an alkyl group having 1 to 6 carbon atoms, a condensed polycyclic aromatic hydrocarbon group which may be substituted with an alkyl group having 1 to 6 carbon atoms, or a hydrocarbon ring aggregate group in which multiple aromatic rings are directly bonded by single bonds (which may be substituted with alkyl groups having 1 to 6 carbon atoms), 2 (This represents a methyl group or an ethyl group.) 【Transformation 3】 (wherein, R 3 and R 4 each independently represent a hydrogen atom or a methyl group, L 1 and L 2 each independently represent an optionally substituted phenylene group or an optionally substituted naphthalenediyl group, L 3 and L 4 each independently represent an alkylene group having 1 to 6 carbon atoms, and m and n each represent 0 or a positive integer such that m+n is from 0 to 40.)

5. The aforementioned cladding, (D) A cured product of a cladding composition comprising a fluorene skeleton-containing epoxy compound and (G) a photoacid generator. The (D) fluorene skeleton-containing epoxy compound is a compound represented by the following formula [4]. The optical waveguide according to claim 1. 【Chemistry 4】 (In formula [4], L 5 and L 6 Each of these independently represents a naphthalenediyl group which may have substituents, p and q each independently represent integers between 0 and 10.

6. A method for manufacturing an optical waveguide according to any one of claims 1 to 5, The first step in forming the lower cladding, A second step involves forming a patterned core on the lower cladding. A third step is to form the upper cladding so as to join it with the lower cladding and cover the core. A fourth step is to form a protective layer on the necessary outer surface portion of the upper cladding or lower cladding. A manufacturing method that includes this.

7. The manufacturing method according to claim 6, wherein the fourth step is a step of forming a protective layer by sputtering.

8. The manufacturing method according to claim 7, wherein the protective layer has a thickness of 0.1 to 0.5 μm.

Citation Information

Patent Citations

  • Optical waveguide-forming photosensitive epoxy resin composition, optical waveguide-forming photosensitive film, optical waveguide produced using the same, and hybrid flexible printed wiring board for optical / electrical transmission

    JP2020020927A

  • Composition for forming optical waveguide which contains reactive silsesquioxane compound

    WO2018199305A1

  • Composition for forming optical waveguide

    WO2023277016A1